ESTRATÉGIAS E PRÁTICAS DE GESTÃO ORIENTADAS À SUSTENTABILIDADE ORGANIZACIONAL: UM ESTUDO DE CASO EM UMA COOPERATIVA DE CRÉDITO - Penteado, Tatiane Aparecida (2019)
The economic, social and environmental development brings reflections to society and organizations, creating new demands and constraints to the activity of cooperatives. Increasingly, the competitiveness of organizations is focused on an oriented management towards sustainability, which aggregates environmental preservation and social and responsible actions, besides the economic growth. The corporate world has an essential role to guarantee the preservation of the environment and in the definition of life quality in its employees’ communities. Socially responsible companies are generators of value for those who are nearby. With this, they achieve better results to themselves. Therefore, the following issue of the research is arisen: what are the existing relations in a rural credit cooperative among the strategic actions and the management practices of the managers and workers in the economic, social and environmental dimensions of sustainability? From this questioning, the main objective of the study is established, which seeks to analyze the relations among the strategic actions of a rural credit cooperative and the management practices in the economic, social and environmental dimensions of sustainability, aiming at identifying and describing the existing sustainability practices in the credit cooperative and finding out the range in which the strategic intentions and management practices, related to economic, social and environmental dimensions of sustainability, are appropriated to the Rural Credit Cooperative. Thus, the constructs of strategic intention and management practices related to economic, social and environmental dimensions of organizational sustainability were examined. The theoretical framework of this study was constituted as to subsidize the knowledge about strategy concepts such as practice and the dimensions of sustainability. This study was developed in the process of descriptive and analytical nature. To investigate the relations among the constructs, a data collection was carried out through survey data from 11 agencies which belong to Cresol Vale das Araucárias Cooperative and 2 interviews with the cooperative managers. The statistical treatment of the data of the sample, obtained from the cooperatives, was carried out by using the software SPSS. Techniques such as descriptive statistics and correlation were used. The main results achieved in the study indicate positive relation among the constructs, management strategy and practice in all the dimensions of sustainability, being stronger in the social and economic dimensions. Regarding the intervening variables discussed namely profile, size, age and location, it was possible to identify that they perform different influences in the relation with the constructs. Through content analysis from the interviews, it was possible to identify strategies and some sustainability practices, as well as to identify the creation process of strategies in the cooperative.